2004
DOI: 10.1634/theoncologist.9-4-451
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Darbepoetin Alfa Versus Epoetin Alfa in Patients with Chemotherapy-Induced Anemia Treated in Clinical Practice

Abstract: Primary Purpose. The objective of this retrospective observational cohort study was to compare the effectiveness of darbepoetin alfa with that of epoetin alfa in patients with chemotherapy-induced anemia using data from noncontemporaneous chart audits conducted at a community-based oncology practice.Materials and Methods. For the first chart audit, data were collected from consecutive patients with nonmyeloid malignancies with diagnoses of chemotherapyinduced anemia and hemoglobin levels ≤10.5 g/dl who were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 15 publications
(17 reference statements)
2
22
0
Order By: Relevance
“…Several clinical studies [4][5][6] have been conducted to gain insight into optimizing the dose and schedule of hematopoietic supports to improve management of chemotherapy-related anemia. In addition, the importance of baseline hemoglobin values at the start of erythropoietic therapy and the timing of erythropoietic treatment relative to application of chemotherapy have been recognized [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies [4][5][6] have been conducted to gain insight into optimizing the dose and schedule of hematopoietic supports to improve management of chemotherapy-related anemia. In addition, the importance of baseline hemoglobin values at the start of erythropoietic therapy and the timing of erythropoietic treatment relative to application of chemotherapy have been recognized [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…9 Darbepoetin alfa is now being used extensively to treat anemia associated with chronic renal insufficiency and chemotherapy. 10,11 Because darbepoetin alfa activates the EPO receptor, we hypothesized that it should also confer neuroprotection in stroke.…”
mentioning
confidence: 99%
“…Studies and clinical practice guidelines have shown that darbepoetin alfa can effectively ameliorate anemia in oncology patients when administered at intervals ranging from once a week to once every three weeks. [1][2][3][4][5]8,[11][12][13] This creates the potential for a flexible dosage regimen that can be aligned with a patient's cancer chemotherapy schedule, enabling both erythropoietic therapy and chemotherapy to be administered during the same visit. This, in turn, increases the time available for seeing other patients, potentially generating further income for the hospital or clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage equivalence between epoetin alfa (40,000 units weekly) and darbepoetin alfa (200 μg every two weeks or 100 μg weekly) for the oncology patients was determined with data gathered from published clinical trials, MUE data, and national guidelines. [1][2][3][4][5]8 In the nephrology setting, the dosage conversion recommended in the darbepoetin alfa package insert was used. 9 Support from administration.…”
Section: Analysis and Resolutionmentioning
confidence: 99%